The occupational meaning of everyday activity for people with severe and enduring mental illness - Milbourn, Benjamin Tyler (Curtin University, 2015)
This hybrid thesis explores the qualitative, longitudinal findings of everyday activities for people diagnosed with a severe mental illness (SMI) living in Western Australia and receiving assertive community treatment services. Over 12 months, SMI consumers’ quality of life appeared episodic and severely compromised. In response to the research findings, the author proposes a framework of everyday engagement to facilitate therapeutic relationships grounded in a consumers’ everyday life that build well-being and recovery experiences.